Sustainable synthesis of eucalyptus globulus – titanium-magnesium nano composite ('EuTiMg NC’) for the photocatalytic degradation of methylene blue - Amrutha Satti; Dinesh Nilikonda; Madhuri Yarlagadda; Naveen Reddy Gade; Rao Poiba Venkata; Vangalapati Meena (E3S Web of Conferences, 2024)
Synthetic dyes that escape into the environment haphazardly endanger both human health and ecosystems. Because of its toxicity and endurance, methylene blue (MB) stands out amongst these dyes as a significant contaminant. Conventional dye removal techniques can entail expensive and energy-intensive procedures. However, there has been a rise in interest recently in investigating sustainable and environmentally suitable substitutes for dye degradation. Because of their availability, affordability, and innate capacity to interact with contaminants, natural materials like leaves have become increasingly attractive options for restoration of the environment. Eucalyptus Globulus blended with titanium and magnesium nanoparticles to yield a novel environmentally friendly composite, 'EuTiMg'. The degradative capacity of the composite against methylene blue, a prevalent pollutant in water, was assessed by a range of analytical methods, such as SEM, TGA, FTIR, and BET analysis. To increase the composite’s photocatalytic activity, we also used Response Surface Methodology (RSM) to optimize the synthesis process. According to our research, 'EuTiMg' composite exhibits better pollutant degrading efficiency and is environmentally benign, making it a viable sustainable option for water treatment applications.